A survey on clinical presentation and nutritional status of infants with suspected cow' milk allergy - Araujo Gabriela TB; Nudelman Victor; Cardoso Ary L; Toporovski Mauro S; Spolidoro José VN; Morais Mauro B; Vieira Mário C; Fonseca Marcelo CM (BMC, 2010)
Abstract Background Cow's milk is the most common food allergen in infants and the diagnosis of cow's milk allergy is difficult, even with the use of several diagnostic tests. Therefore, elimination diets and challenge tests are essential for the diagnosis and treatment of this disorder. The aim of this study is to report the clinical presentation and nutritional status of children evaluated by pediatric gastroenterologists for the assessment of symptoms suggestive of cow's milk allergy. Methods An observational cross-sectional study was performed among 9,478 patients evaluated by 30 pediatric gastroenterologists for 40 days in 5 different geographical regions in Brazil. Clinical data were collected from patients with symptoms suggestive of cow's milk allergy. The nutritional status of infants (age ≤ 24 months) seen for the first time was evaluated according to z-scores for weight-for-age, weight-for-height, and height-for-age. Epi-Info (CDC-NCHS, 2000) software was used to calculate z-scores. Results The prevalence of suspected cow's milk allergy in the study population was 5.4% (513/9,478), and the incidence was 2.2% (211/9,478). Among 159 infants seen at first evaluation, 15.1% presented with a low weight-for-age z score (< -2.0 standard deviation - SD), 8.7% with a low weight-for-height z score (< -2.0 SD), and 23.9% with a low height-for-age z score (< -2.0 SD). Conclusion The high prevalence of nutritional deficits among infants with symptoms suggestive of cow's milk allergy indicates that effective elimination diets should be prescribed to control allergy symptoms and to prevent or treat malnutrition.